The role and mechanism of irisin/NLRP3 signal in aerobic exercise ameliorating blood glucose homeostasis in pre-diabetic mice - Shujuan Hu; Zhengkang Wu; Xuan Liu; Yiting Ding; Jun Chen; Xianwang Wang (PLoS ONE, 2025)
Pre-diabetic mellitus (PDM) is characterized by chronic low-grade inflammation, primarily driven by NLRP3 inflammasome hyperactivation and a concurrent deficiency of the myokine irisin. MCC950 is a highly specific inhibitor of the NLRP3 inflammasome, and aerobic exercise has also been shown to effectively suppress its activation. However, the underlying molecular mechanisms remain unclear. The aim of this project was to explore whether the irisin/NLRP3 signaling pathway was regulated by aerobic exercise in mice with PDM. Forty mice were divided into: the common diet group (DC group, N = 10), and the high-fat diet group (HFD group, N = 30). The HFD group received a high-fat diet combined with a single low-dose streptozotocin (STZ) injection to induce a pre-diabetic state. Successfully modeled mice were identified as PDM mice and randomly assigned into three subgroups: the PDM control group (PDM-DC group, N = 8), the PDM plus exercise group (PDM-EX group, N = 8), and the PDM plus MCC950 group (PDM-MC group, N = 8). The PDM-EX group performed treadmill exercise for 4 weeks (5 days/week, 12 m/min, 60 min/d). The PDM-MC group received NLRP3 inhibitor injections (MCC950, 10 mg/kg, 5 d/week) for 4 weeks. These results found that aerobic exercise and MCC950 ameliorated glycolipid metabolism, reduced insulin levels, and effectively facilitated the skeletal muscle remodeling in PDM mice. Compared with the DC group, PDM mice exhibited significantly downregulated FNDC5 /irisin expression and upregulated NLRP3 and IL-18 expression ( P < 0.05 or P < 0.01). Notably, aerobic exercise significantly increased FNDC5 /irisin expression ( P < 0.05), and decreased NLRP3 and IL-18 levels ( P < 0.01). Cell experiments revealed that the mRNA and protein expression of NLRP3, IL-1β and IL-18 in the high glucose (HG) condition were higher compared with the lower glucose (CON) condition ( P < 0.01). Treatment with irisin significantly attenuated these increases ( P < 0.05 or P < 0.01). These findings demonstrate that aerobic exercise alleviates inflammation and ameliorates glycolipid metabolism in PDM mice by modulating the irisin/NLRP3 signaling pathway. Moreover, irisin effectively suppresses high glucose-induced upregulation of NLRP3, IL-1β, and IL-18, suggesting its potential therapeutic role in managing pre-diabetic inflammation.